Canine POMC deletion (p187fs) allele frequency in labrador retrievers in Brazil - Lourenço, Natalia O. [UNESP]; Albuquerque, Ana Luísa H. [UNESP]; Basso, Roberta M. [UNESP]; Trecenti, Anelize S. [UNESP]; Albertino, Lukas G. [UNESP]; Melchert, Alessandra [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, José P. [UNESP] (FapUNIFESP (SciELO), 2019)
The Labrador Retriever is among the main breeds with the greatest predisposition to obesity. Several factors, especially the interrelationships between food management, exercise and social factors; influence the likelihood of a dog becoming obese. Furthermore, genetic factors are also responsible for obesity in dogs, and in Labrador Retriever, a frameshift mutation (P187fs) in pro-opiomelanocortin (POMC) gene is strongly associated with obesity. There is no knowledge of studies that have previously evaluated the prevalence of the canine POMC deletion (P187fs) in Brazilian Labrador Retriever. Therefore, the objective of this study was to investigate this mutation in Labrador Retriever dogs in Brazil. Of the 108 Labrador Retrievers that were assessed in this study, 59 were from a previous study, composed by animals assisted in a veterinary hospital with unknown lineage, and 49 were from a prospective study, composed of 19 pet and 30 assistance/rescue Labrador Retriever dogs. The obesity risk and appetite questionnaire were applied, with some modifications, to tutors of the animals used in the prospective study. Fragments of the DNA, containing the mutation, were amplified by PCR and submitted to direct gene sequencing. The allele frequency of the mutation was 21.3% and was out of Hardy-Weinberg equilibrium (P<0.05). Using only the data of animals with known lineage, the presence of the mutated allele was higher in the Assistance/rescue Group than Pet Group (P<0.01), furthermore, the allele frequencies observed in Assistance Group (31.7%) was out of Hardy-Weinberg equilibrium (P<0.05), while that in the Pet Group (18.4%) was in equilibrium (P>0.05). Although the mutation has increased the food-motivation in the assistance/rescue dogs, other variables, especially frequent exercising, favored that these animals maintained the ideal body weight (body condition score = 5). In summary, the Hardy-Weinberg disequilibrium observed in the allele distribution of the deletion POMC_P187fs in this study, independently of the Labrador Retriever group assessed, suggesting the possibility of positive selection of the mutated allele, which may lead to the maintenance of this deleterious allele in the studied population.
Frequência de alelos mutados (P187fs) no POMC de cães Labrador Retriever no Brasil